Wi-Fi positioning system - Guo, Ruiliang. (2011)
A Wi-Fi positioning system based on the Client-Server architecture has been developed during the previous project. A basic client application for Windows CE and XP platform and the server software running the Linux operating system has been built. Presented in this report is an enhanced design and improved development for Wi-Fi Positioning System.